המולדת ההטרוטופית של נסים אלוני - עוז, אברהם (מכאן, 2006)
The work of Nissim Aloni is constantly courting the inconstant.At the outset of his dramatic career he explored the functions ofalienation between man and his place, and from there he proceededto the homeless existence of the exiles of The American Princess,until settling permanently in the heterotopic twilight zone of hislater plays. The collective hegemony in Aloni's plays is nothingbut a facade, and the family infiltrates the historical narrative as adecisive answer to the false national community. The nation doesnot play any material role in Aloni's work: it is placed beyond theconceptual horizon of the characters. Its traces can be recognisedin narrower communities, such as that of the family, which in turnis also a game in which everyone loses, and first and foremost- family unity. The biological family is shown as nothing but anOedipal nest of wasps; and the Mafia family as nothing but anorganisation of beggar-murderers. On a deeper level, however,Aloni's families are far from being ultimate, final concepts, butare, rather, metonymies of the imagined community inhabitingthe national motherland: an ideological association disguised as acoherent genetic community. Thus the historical narrative of Aloni'sclowns constitutes an imaginary world of illusions, counterfeit andworthless plots, a narrative of comedy and melodrama, not basedon any conventional reality, but bursting into the world by virtue ofritual and myth